Assessment of the Correlation between the Salivary Flow Rate and Dental Caries Experience among Children with ?-Thalassemia Major - Mudhafar Fadhil Jaddoa1, Alhan Ahmed Qasim2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Thalassemia constitutes a group of congenital blood disorders which characterized by a defect in synthesis of one or more globin chains of human hemoglobin molecule and the resultant microcytosis and hypochromia of the RBCs. It is of two main divisions, ?- and ?-thalassemia and several other subdivisions. The study group composed of 40 patient years previously diagnosed with ?-thalassemia major attending the thalassemia center in Thi-Qar province/Iraq. The control group, matching the age and sex of the study group, and consisted from 40 child selected from a number of primary schools. Unstimulated salivary samples was taken from each subjects under standardized conditions. The mean value of flow rate of saliva was lower among ?-thalassemias (0.466±0.024) than for controls (0.829±0.048). The (mean±SE) for the primary teeth (dmfs) in ?-thalassemias (1.450±0.324) was higher than that for controls (1.250±0.808), this difference was not significant (P> 0.05). The (mean±SE) of the caries experience (DMFs) in ?-thalassemias (6.850±0.782) was higher than for the control group (3.600±0.489).